Optimization of RoRo (Roll On-Roll Off) Ship Berthing Scheduling Using the Berth Allocation Problem (BAP) Model at Parit Rempak Port, Karimun Regency - Arianti, Nisha Desfi; Sitompul, Mey Krisselni; Syahfina, Wulan; Rahmania, Selvika Putri; Pransiska, Ryryn; Zerrand, Leonardo (Techno.Com, 2025)
Parit Rempak RORO Port is one of the sea transportation hubs that serves inter-regional connectivity in Karimun Regency. The limitations of the dock infrastructure, such as a length of 100 meters and a width of 11 meters, pose challenges in managing ship berthing schedules, especially RORO type ships. This study aims to analyze the suitability of the dock capacity to the ship operational schedule using the Berth Allocation Problem (BAP) approach. The BAP model is compiled and simulated through the Python-based Google Colaboratory platform to avoid scheduling conflicts and minimize ship waiting time. The simulation results are displayed in the form of a Gantt Chart which shows that the four ships: KMP Teluk Singkil 1, KMP Teluk Singkil 2, KMP Tandemand, and KMP Kundur can be scheduled sequentially without overlapping berthing times. Spatial analysis of the length and width of the dock also shows that this port is ideal for serving one ship at a time. This study shows that digitalization of the scheduling system can be an efficient solution in optimizing dock operations.   Keywords - RORO Port, Berth Allocation Problem, ship scheduling, Google Colab, dock optimization